Sophia – the Personification of Divine Wisdom in the Culture of Novgorod the Great from 13th to 15th Century - Brzozowska, Zofia (Studia Ceranea, 2014)
The idea of Sophia – the personified Wisdom of God served as a symbol of independence and identity of the republic in the political culture of Novgorod the Great. In Old Russian chronicles and other narrative sources which can be connected with Novgorod, one may find statements showing that – in the eyes of the Novgorodians themselves – Wisdom was not only one of the main attributes of God, but also a separate character, a kind of divine being, who could be interpreted as patronesses and supernatural protector of the city-state. Construction of the temple of Hagia Sophia in Novgorod is usually dated to 1045–1050. In the source material one can find information that Novgorodian Sophia church was undoubtedly the most significant and important monument in the city. The theme of Wisdom of God is also a very prominent topic in Novgorodian historiography and literature. Moreover, the feminine personification of God’s Wisdom can also be found on the coins, emitted by the city-state from 1420.